Persepsi Kemanfaatan dalam Penggunaan BSI Mobile oleh Generasi X, Y dan Z - Alsya Syaepana; Verbena Ayuningsih Purbasari (Institut Agama Islam Negeri Ponorogo, 2024)
Introduction: In this era of rapid technological development, the number of BSI mobile users is still very small. And many customers do not use BSI Mobile even though they have the application. Then there are field facts that show differences with the theory of attitudes towards technology by generations X, Y and Z. So the purpose of this study is to find out how the perception of usefulness by the three generations in the use of BSI Mobile and to find out how the impact of this on the number of BSI Mobile usage. Research Methods: This research is qualitative research and includes the type of research (field research). Results: The results of this study show that generations X and Y have a positive perception of BSI Mobile benefits, which shows that BSI Mobile makes their work faster, increases productivity, makes work performance better, their work is easier, BSI mobile is very useful for them and feels BSI Mobile It is effective. Then also in generation Z they have a perception of expediency that BSI Mobile makes their work faster, makes job performance better, work easier, and feels BSI Mobile is effective. However, generation Z feels that BSI mobile provides less benefits for them and does not increase their productivity. Conclusion: The impact of the perceived usefulness of generations X, Y and Z is an increase in the number of BSI Mobile usage.